Pendekatan Islami dan Psikologis dalam Menangani Stunting: Kajian Multidisipliner terhadap Kesehatan Anak - Mas'ud, Moh. Ali; Fitria, Mulajimatul (CV. Lentera Literasi Indonesia, 2025)
Stunting is one of the chronic health problems that threatens the quality of human resources, especially in children in developing countries such as Indonesia. This condition is not only caused by lack of nutritional intake, but also influenced by low parental awareness in fulfilling children's basic needs and suboptimal parenting patterns. This study aims to examine how Islamic and psychological approaches can synergize in dealing with stunting problems and increasing awareness and the active role of families in maintaining child growth and development. The method used is a literature review by analyzing various sources of scientific literature and relevant theories. The Islamic approach emphasizes the spiritual and moral responsibility of parents in maintaining the child's trust, while the psychological approach provides a scientific understanding of the stages of child development and the importance of a responsive environment. The results of the study show that the integration of these two approaches can form a more complete and effective parenting pattern, thereby strengthening family resilience in efforts to prevent stunting. This study recommends the need for cross-sector collaboration, including health workers, psychologists, and religious figures, in parenting education and family-based stunting intervention programs.